The Civic Labor of Volunteer Moderators Online - Matias, J. Nathan (Social Media + Society, 2019)
Volunteer moderators create, support, and control public discourse for millions of people online, even as moderators’ uncompensated labor upholds platform funding models. What is the meaning of this work and who is it for? In this article, I examine the meanings of volunteer moderation on the social news platform reddit. Scholarship on volunteer moderation has viewed this work separately as digital labor for platforms, civic participation in communities, or oligarchy among other moderators. In mixed-methods research sampled from over 52,000 subreddit communities and in over a dozen interviews, I show how moderators adopt all of these frames as they develop and re-develop everyday meanings of moderation—facing the platform, their communities, and other moderators alike. I also show how this civic notion of digital labor brings clarity to a strike by moderators in July 2015. Volunteer governance remains a common approach to managing social relations, conflict, and civil liberties online. Our ability to see how communities negotiate the meaning of moderation will shape our capacity to address digital governance as a society.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMDU2MzA1MTE5ODM2Nzc4